2009
DOI: 10.1136/qshc.2008.032045
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aviation-style non-technical skills training on technical performance and outcome in the operating theatre

Abstract: Unintended harm to patients in operating theatres is common. Correlations have been demonstrated between teamwork skills and error rates in theatres. This was a single-institution uncontrolled before-after study of the effects of ''non-technical'' skills training on attitudes, teamwork, technical performance and clinical outcome in laparoscopic cholecystectomy (LC) and carotid endarterectomy (CEA) operations. The setting was the theatre suite of a UK teaching hospital. Attitudes were measured using the Safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
313
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(328 citation statements)
references
References 29 publications
9
313
0
6
Order By: Relevance
“…Nevertheless, only 56% (n = 48) of participants felt that the role of radiographers regarding CPR performance is changing positively. A correlation (r = 0.866) was also observed between age and experience, which confirms the correlation between work experience and technical knowledge (24,25). Therefore, according to the study findings, aging increases experience and experience increases the level of technical knowledge.…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, only 56% (n = 48) of participants felt that the role of radiographers regarding CPR performance is changing positively. A correlation (r = 0.866) was also observed between age and experience, which confirms the correlation between work experience and technical knowledge (24,25). Therefore, according to the study findings, aging increases experience and experience increases the level of technical knowledge.…”
Section: Discussionsupporting
confidence: 66%
“…Three studies assessed more than one performance measure. Only two studies indicated all the information to calculate the effect size and they reported one medium 55 and one large effect. 57 …”
Section: Interventions Targeting Team Process Behavioursmentioning
confidence: 99%
“…With the lack of a definitive consensus regarding the desirable conditions of performance assessments, the following factors should be considered when applying performance assessment instruments to residency training: the Sarker's checklist [54,55] Eubanks's checklist [8,26,56] Seynour's unnamed [57,58] OCHRA NOTECHS [22,32,60,61] OTAS [23,62] Original [19,31,59] Misha's [60] Relations to other variables Operative data ?…”
Section: Discussionmentioning
confidence: 99%